A influência do volume na performance dos fundos de investimento em ações no Brasil - Gazaneo, Gustavo Lisandro Vila (2006)
Using the international literature on mutual funds, the present study search to find some characteristics that influence the performance of the equity mutual funds in Brazil from January of 1999 to April of 2005. The main subject of the work is to notice that the equity mutual funds have decreasing return of scale. At the same time, the persistence of a good profitability depends on the degree of the managers' professionalism and also of a good relationship between the responsible manager and the investor, and a great contract betw een both. It was observed, through a regression using panel data, that the volume doesn't have negative influence in the return of the funds, on the contrary, as larger is the fund, better is the profitabil ity of the same. It was also observed that the funds that pay performance incentive to their managers have a better acting than the others. It was identified also that the equity mutual funds that use high water marks as a remuneration incentive to the managers, has profitability than the funds that pay performance, but they don't use the high water marks in the own regulation. It was found that there is a straight relationship between incentive and performance. The results at this study may be used to facilitate the knowledge and the new decisions of researchers, investors, company managers, Brokers and Dealers, pension funds and others interested parties in the industry of investment funds in Brazil.